Impulsivity in Parkinson’s Disease Is Associated With Alterations in Affective and Sensorimotor Striatal Networks - Ruitenberg, Marit F. L.; Wu, Tina; Averbeck, Bruno B.; Chou, Kelvin L.; Koppelmans, Vincent; Seidler, Rachael D. (Frontiers in Neurology, 2018)
A subset of patients with Parkinson’s disease experiences problems with impulse control, characterized by a loss of voluntary control over impulses, drives, or temptations regarding excessive hedonic behavior. The present study aimed to better understand the neural basis of such impulse control disorders in Parkinson’s disease. We collected resting-state functional connectivity and structural MRI data from 21 Parkinson’s disease patients with impulse control disorders and 30 patients without such disorders. To assess impulsivity, all patients completed the Barratt Impulsiveness Scale and performed an information gathering task. MRI results demonstrated substantial differences in neural characteristics between Parkinson’s disease patients with and without impulse control disorders. Results showed that impulsivity was linked to alterations in affective basal ganglia circuitries. Specifically, reduced frontal-striatal connectivity and GPe volume were associated with more impulsivity. We suggest that these changes affect decision making and result in a preference for risky or inappropriate actions. Results further showed that impulsivity was linked to alterations in sensorimotor striatal networks. Enhanced connectivity within this network and larger putamen volume were associated with more impulsivity. We propose that these changes affect sensorimotor processing such that patients have a greater propensity to act. Our findings suggest that the two mechanisms jointly contribute to impulsive behaviors in Parkinson’s disease.